2012
DOI: 10.3389/fnint.2012.00034
|View full text |Cite
|
Sign up to set email alerts
|

The effects of trauma exposure and posttraumatic stress disorder (PTSD) on the emotion-induced memory trade-off

Abstract: Many past examinations of memory changes in individuals with posttraumatic stress disorder (PTSD) have focused on changes in memory for trauma. However, it is unclear if these mnemonic differences extend beyond the memory of the trauma to memory for other positive and negative information and if they are specific to individuals with PTSD or extend to other individuals who have experienced trauma. The present study examined the influences of trauma exposure and PTSD on an effect that may parallel tunnel memory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 56 publications
0
34
1
Order By: Relevance
“…Among studies involving tasks with picture stimuli: five studies used a recognition memory task (Chemtob et al, 1999 ; Whalley et al, 2009 ; Brohawn et al, 2010 ; Mickley Steinmetz et al, 2012 ; Patel et al, 2016 ); one study used a recognition memory task after an oddball task (Guillery-Girard et al, 2013 ); one study used an item-method directed forgetting task (Baumann et al, 2013 ); and another study used a delayed memory free recall test (Nicholson et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among studies involving tasks with picture stimuli: five studies used a recognition memory task (Chemtob et al, 1999 ; Whalley et al, 2009 ; Brohawn et al, 2010 ; Mickley Steinmetz et al, 2012 ; Patel et al, 2016 ); one study used a recognition memory task after an oddball task (Guillery-Girard et al, 2013 ); one study used an item-method directed forgetting task (Baumann et al, 2013 ); and another study used a delayed memory free recall test (Nicholson et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies implicate semantic processing in PTSD (Pineles, Shipherd, Welch, & Yovel, 2007 ; McNally et al, 1990 ; Weber, 2008 ). One study in particular observed that TE, PTSD-negative participants showed less emotion-induced memory trade-off for emotional items in a memory task, compared to both PTSD-positive and non-TE participants, indicating an emotional semantic encoding resilience factor (Mickley Steinmetz et al, 2012 ). Memory processes were also implicated in an fMRI study by Geuze Vermetten, Ruf, De Kloet, and Westenberg ( 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…The local-global task (or "Navon task") can be administered in two ways, assessing either divided or focused attention/inhibition (Fink, et al, 1996). We used the latter version because attention narrowing and impaired inhibition are considered important predictive factors in threat processing and PTSD development (Easterbrook, 1959;Janovic & Ressler, 2010;Mickley Steinmetz, Scott, Smith & Kensinger, 2012).…”
Section: Introductionmentioning
confidence: 99%